2019
DOI: 10.1177/0734242x19872263
|View full text |Cite
|
Sign up to set email alerts
|

Lead recovery from spent lead acid battery paste by hydrometallurgical conversion and thermal degradation

Abstract: Spent lead paste is the main component in lead-acid batteries reaching end of life. It contains about 55% lead sulphate and 35% lead dioxide, as well as minor amounts of lead oxide. It is necessary to recycle spent lead paste with minimal pollution and low energy consumption instead of the conventional smelting method. In this study, a novel approach involving hydrometallurgical desulphurisation and thermal degradation is developed to recover lead as PbO products from spent lead acid batteries. First, the desu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The pyrometallurgical method is widely used for the recycling of waste lead paste, and it is currently a mature technology [47]. Generally, this method involves high-temperature treatment of the spent lead paste and the addition of a reducing agent such as coke to promote the reduction reaction of the lead paste in a molten state [37,47]. The pyrometallurgical method can be further classified into one-step and two-step processes.…”
Section: Pyrometallurgical Processmentioning
confidence: 99%
“…The pyrometallurgical method is widely used for the recycling of waste lead paste, and it is currently a mature technology [47]. Generally, this method involves high-temperature treatment of the spent lead paste and the addition of a reducing agent such as coke to promote the reduction reaction of the lead paste in a molten state [37,47]. The pyrometallurgical method can be further classified into one-step and two-step processes.…”
Section: Pyrometallurgical Processmentioning
confidence: 99%
“…[42] Therefore, research on the recycling technology of LIB cathode materials was intensive, which may be related to the retired LIB cathode materials that are rich in valuable metals and have high environmental and economic benefits. [43] In addition, the number of literature on lead-acid batteries recycling ranked second [35,44] (87 articles, accounting for 9.60%), while the numbers of literature on Ni-MH batteries [45] (66 articles, accounting for 7.41%), Ni-Cd batteries [46] (45 articles, 4.97%), and mixed batteries materials (39 articles, 4.30%) were less. [47] The types and compositions of rechargeable battery recycling literature are shown in Figure 10b.…”
Section: Analysis Of the Composition Of Literature Publishing Techniquesmentioning
confidence: 99%
“…In previous studies, researchers have tried to convert SLP into lead products such as metallic lead, organic lead compounds, , lead oxide, , lead chloride, , lead iodide, and lead sulfide. Yang et al used a combination of wet desulfurization and a roasting process to prepare lead oxide products . Liu et al reported on a vacuum chlorination process with calcium chloride as a reagent to successfully produce high-purity lead chloride products .…”
Section: Introductionmentioning
confidence: 99%
“…24−26 The global objective of decarbonization also has presented fresh challenges in the low-carbon reutilization of spent LABs. 27−29 In previous studies, researchers have tried to convert SLP into lead products such as metallic lead, 30−34 organic lead compounds, 35,36 lead oxide, 35,37−46 lead chloride, 47,48 lead iodide, 49−51 and lead sulfide. 52−54 Yang et al used a combination of wet desulfurization and a roasting process to prepare lead oxide products.…”
Section: ■ Introductionmentioning
confidence: 99%